Covid-19 Pandemic Shutdown: Challenges of Hei’s Electronic Support Services in Teacher Education Programs - Imran Latif Saifi (International Islamic University Islamabad, 2021)
Coronavirus 2019 (COVID-19) is the result of acute respiratory syndrome coronavirus 2 (SARSCoV-2). Pandemic is the outburst of any disease worldwide. Electronic Service (E-service) is based on technology and provides different electronic channels i.e. e-learning & coaching (online learning), e-library, etc. This study was design to explore challenges of HEI’s electronic support services in teacher education during pandemic shut down of COVID-19. The objectives of the study were to explore the challenges of e-support services in teacher education programs due to pandemic shutdown of COVID-19 and to propose a framework for stake holders of HEI’s esupport services. This study was descriptive and the survey method was used. Teacher education program B. Ed (1.5 Years) from two universities of Pakistan, one from formal mode and one from distance education online mode were selected and all the prospective teachers of 2nd semester were defined as population of the study. Sample of the study consisted of 150 students (selected conveniently). An online questionnaire was used as tool for data collection which had 15 closeended statements on 5- point Likert scale. It was concluded that the facility to purchase internet bundles was not available to students in the pandemic shutdown of COVID-19. The students and academia on the other hand were not trained for online teaching learning procedures. It was proposed that HEI’s may arrange internet bundles with collaboration of internet provider companies to students, academia and institutions also focus to train academia and students for online education because the effect of COVID-19 Pandemic Shutdown are expecting a change in future procedures of education till the situation is not going to be seen normal.